2013
DOI: 10.1111/mve.12027
|View full text |Cite
|
Sign up to set email alerts
|

Larval salinity tolerance of two members of the Anopheles funestus group

Abstract: The Anopheles funestus group (Diptera: Culicidae) is one of the main species groups involved in malaria transmission in the Afrotropical regions. Basic research into this group has been limited because its members are eurygamic (they tend not to mate in confined spaces), which makes laboratory colonization difficult. Currently, only a few An. funestus Giles colonies are available and no colonies of other members of the group have been established. As information on the larval biology of members of the An. fune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Despite a relatively high salinity of 110 mg/l in Possotômè water, more than 70% of adults were able to emerge. This correlates with the observation of Koekemoer et al , (2014) 31 , where they reported that salinity does not affect the emergence of An. funestus adults.…”
Section: Discussionsupporting
confidence: 92%
“…Despite a relatively high salinity of 110 mg/l in Possotômè water, more than 70% of adults were able to emerge. This correlates with the observation of Koekemoer et al , (2014) 31 , where they reported that salinity does not affect the emergence of An. funestus adults.…”
Section: Discussionsupporting
confidence: 92%
“…parensis have been observed to share aquatic habitats with An. funestus [ 31 ], though there can be differences in their level of tolerance to salinity [ 55 ]. Consequently, larval source management (LSM) targeted An.…”
Section: Introductionmentioning
confidence: 99%
“…funestus group is broadly distributed across Africa, with its major species, An. funestus , widely distributed over subtropical and tropical Africa where it breeds in permanent large water bodies with emergent vegetation [ 7 , 11 ]. Anopheles funestus is highly anthropophilic (human biting) and exhibits endophilic (indoors) feeding and resting behaviours [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%